Religion of Common People and the Potential of Radicalism among Hinterland and Coastal Communities in East Java - Rr. Suhartini; Ali Nurdin; Mufti Labib (Islamica: Jurnal Studi Keislaman, 2022)
This study aims to identify community religious traditions and opportunities for radicalization in inland and coastal communities of East Java. The method uses mixed methods and a qualitative model to describe the community’s religious traditions and the potential for radicalization. Meanwhile, data was collected by semi-open interviews with 110 informants, analyzed using a flow model and calculated using descriptive statistics. According to the study’s findings, East Java’s religious practices in both inland and coastal communities are manifested in the traditions of aqīdah, muā‘malah, and worship rituals. Traditions of aqidah are carried out with the understanding ahl al-Sunnah wa al-Jamā‘ah that was developed by Nahdlatul Ulama and Muhammadiyah. Mu‘āmalah (social) tradition is based on the teachings of Kiai, teachers, and parents and is based on local wisdom. Ritual worship follows the understanding of Ahl al-Sunnah wa al-Jamā‘ah, which means performing mah}d}ah worship in a disciplined fashion: prayer, zakat, fasting during Ramadan and performing hajj for those who can afford it. Additionally, the map shows the chance of being radical and moderate in both the inland and coastal communities in East Java; the chance of radicalism is 21.60%, of being uncertain is 13.13%, and of being moderate is 65.28%.